A neuro-cognitive model of comprehension based on prediction and unification - Blache, Philippe (Frontiers in Human Neuroscience, 2024)
Most architectures and models of language processing have been built upon a restricted view of language, limited to sentence processing. These approaches fail to capture one primordial characteristics: efficiency. Many facilitation effects are known to be at play in natural situations such as conversation (shallow processing, no real access to the lexicon, etc.) without any impact on the comprehension. We present in this paper the basis of a new model integrating into a unique architecture these facilitation effects for accessing the meaning into the classical compositional architecture. This model relies on two mechanisms, prediction and unification, and provides a unique architecture for the description of language processing in its natural environment.